Rancang Bangun Aplikasi Sistem Informasi Pariwisata di Kabupaten Maluku Tenggara Berbasis Web dengan Metode User Centered Design (UCD) - Rawulunubun, Domitila; Faizah, NM; Koryanto, Lucky (Yayasan Kawanad, 2024)
This research is motivated by the necessity for an information system capable of providing comprehensive, fast, and accurate tourism information for Southeast Maluku Regency. The current dissemination of tourism information within the regency is limited, hindering potential visitors from outside the area from accessing valuable insights. The proposed information system aims to bridge this gap by offering a web-based platform that facilitates the management of tourism and cultural information by the local government’s tourism and culture department. Utilizing the user-centered design (UCD) methodology, the system is developed using programming languages such as PHP and is supported by a MySQL database for data storage. This tourism information system includes features that allow users to search for information related to cultural tourism and culinary experiences in the region. It is anticipated that the implementation of this system will significantly enhance the promotion of Southeast Maluku tourism sector to a wider audience.